USERâ€™S OPINIONS ON ANDROID-BASED LEARNING - Marko Ayaki Lumbantobing; Muhammad Hudan Rahmat (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
The purpose of this research is to find out the user's response to e-module based on android products to facilitate learning process. Likert scale with four variations of the answer was the scale used in this study. Research data were analyzed by quantitative descriptive. The result of the research showed that e-module based on android products have met the eligibility criteria with the category "very good" so it is worth to use. The data of the research showed that Userâ€™s response to e-module in this case teachers and students obtained â€œvery goodâ€ category with the feasibility percentage of each are 84.38% and 81.67%.